MAPPENRE' DUI' IN BUGIS BONE MARRIAGE, SOUTH SULAWESI: BETWEEN ISLAMIC LAW AND CULTURAL CHANGE - Anissa Sharfina; Abdulahanaa; Wardanah Said; Dedy Sumardi (Master Program of Sociology, Universitas Malikussaleh,, 2026)
Islamic legal principles in the contemporary era. It aims to describe the practice of mappenre' dui' in Tanete Riattang District, Bone, and to analyze its conformity with Islamic teachings. Employing a qualitative methodology, data were collected through in-depth interviews with customary leaders, heads of religious affairs offices, and community members, as well as through documentary review. The analysis was conducted thematically using a sociological-legal approach. The findings reveal that mappenre' dui' carries positive value as a cultural heritage that reinforces kinship ties, respect, and familial responsibility. Nevertheless, its contemporary practice frequently gives rise to Shari'a-related concerns, including the presence of the prospective groom, the exchange of rings, pre-marital physical interaction, and a tendency toward extravagance in ceremonial proceedings. This situates the tradition in a dilemma: on one hand, it remains broadly compatible with Islamic law through its social values; on the other, it risks deviation if left unregulated. Drawing on the sociology of Islamic law, the study argues that mappenre' dui', amid ongoing cultural change, may be preserved as authentic 'urf (customary practice) provided it is implemented in accordance with the principles of simplicity, protection of honor, strengthening of social solidarity, and avoidance of practices that contravene Islamic law.